Athletic injury and minor life events: A prospective study - Fawkner, H. J.; McMurrary, N. E.; Summers, J. J. (Journal of Science and Medicine in Sport, 1999)
Summary In the past several years, there has been an upsurge of research related to the psychology of athletic injury; that is, there has been an interest in how psychology influences the incidence of and rehabilitation from athletic injury. This study examined the relationship between hassles or minor life events and athletic injury. It was hypothesized that an athlete with many stressors, when placed in a stressful situation, (competition, hard workout) is likely to have a high stress response (tension, distractability) which relates to the incidence of injury. Ninety-eight athletes from the sports of field hockey, volleyball, and triathlon participated in the study. Specifically, each week throughout the season, athletes completed the 53 item Daily Hassles Scale which measures the effect (hassle to uplift) of a variety of life events such as family issues, personal relationships, work, health, and finances. The incidence of injury, defined as a medical problem that caused a restriction in training for at least one day, was recorded throughout the season. Statistical analyses were conducted to assess differences in "hassles/ minor life events" in baseline versus the week prior to injury. Additionally, comparisons were conducted on the fluctuations in hassles scores of injured versus uninjured athletes. Findings Statistically significant and meaningful results were found. Specifically, it was found that non-injured athletes experienced little fluctuation in their hassles scores throughout the season. Furthermore, for injured athletes the intensity of hassles reported increased immediately prior to the injury. This increase was statistically significant when compared to the individual athletes baseline (normal) level. Implications Increases in minor life events appear to be a reliable predictor of athletic injury. It seems critical to monitor these minor life events in athletes and intervene when increases in these "stresses" occur. This intervention could relate to implementing stress management strategies or decreasing the training stress. Remember that athletes do not live and train in a vacuum. Rather, they are influenced (positively and negatively) by a multitude of social, environmental, and personal factors. Take these factors into account in the training of individual athletes as too much combined stress will eventually lead to a "breakdown".